Third approximation of time-dependent controller parameter in fokker-planck PDF: applications in robotics - Ismail Mageed (Computational Algorithms and Numerical Dimensions)
The behavior of the Time-Dependent Controller's Designed Parameter (TDCDP) third approximation is a challenging open problem that has never been fully answered in the literature to date. By advancing control theory and related interdisciplinary fields, this innovative paper will substantially contribute to contemporary control theory. Engineers and industry professionals who want to learn more about the latest developments in control theory settings will find the study very helpful. Control theory is essential to these domains. On the other hand, there is a wide range of fields in which Fokker Planck Kolmogorov (FPK) equations are applied. Consequently, the study immediately acquires greater taste and legitimacy. Some potential applications of FPK equations to robotics are highlighted. The study concludes with several interesting unresolved questions, some closing thoughts, and suggestions for additional research.